2022
DOI: 10.1038/s41467-022-31782-7
|View full text |Cite
|
Sign up to set email alerts
|

Constrained CMIP6 projections indicate less warming and a slower increase in water availability across Asia

Abstract: Climate projections are essential for decision-making but contain non-negligible uncertainty. To reduce projection uncertainty over Asia, where half the world’s population resides, we develop emergent constraint relationships between simulated temperature (1970–2014) and precipitation (2015–2100) growth rates using 27 CMIP6 models under four Shared Socioeconomic Pathways. Here we show that, with uncertainty successfully narrowed by 12.1–31.0%, constrained future precipitation growth rates are 0.39 ± 0.18 mm ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…For the future climate scenarios, we use a multi‐model ensemble consisting of five GCMs listed in Table S1 of Supporting Information S1 under three SSPs (i.e., SSP1‐26, SSP3‐70, and SSP5‐85) from the latest CMIP6. Numerous studies have found that the raw outputs of precipitation and temperature from CMIP6 climate models are overestimated in Asia and have non‐negligible uncertainties (Chai et al., 2022). To reduce the systematic biases of climate models, we use the bias‐corrected daily outputs from the Intersectoral Impact Model Intercomparison Project 3b (ISIMIP3b).…”
Section: Data Descriptionmentioning
confidence: 99%
“…For the future climate scenarios, we use a multi‐model ensemble consisting of five GCMs listed in Table S1 of Supporting Information S1 under three SSPs (i.e., SSP1‐26, SSP3‐70, and SSP5‐85) from the latest CMIP6. Numerous studies have found that the raw outputs of precipitation and temperature from CMIP6 climate models are overestimated in Asia and have non‐negligible uncertainties (Chai et al., 2022). To reduce the systematic biases of climate models, we use the bias‐corrected daily outputs from the Intersectoral Impact Model Intercomparison Project 3b (ISIMIP3b).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Precipitation and temperature largely determine the snowfall and snowmelt rates, producing large effects on snowpack 4 . However, temperature and precipitation of ESM simulations still have systematic biases 54 . The Community Earth System Model Version 2 (CESM2) forcing data used in this study shows an overall consistent trend of future precipitation and air temperature projections over the TP with the ensemble mean of the used CMIP6 models (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The constrained GSAT warming is useful for other climate quantities that scale well with GSAT change (Hu et al., 2021; Lee et al., 2021). The projections of local temperature and water availability over the Artic and Eurasian continents can be constrained by using the observed GSAT warming trend (Chai et al., 2022; Hu et al., 2021; Ribes et al., 2022). In addition, combining the observed evidence of global and regional warming can refine the regional projection assessment (Qasmi & Ribes, 2022; Ribes et al., 2022).…”
Section: Introductionmentioning
confidence: 99%